NEW GENETIC SOURCES OF CYTOPLASMIC MALE STERILITY OF ONIONS (Allium cepa L.) - A. N. Logunov; M. V. Budylin; E. A. Tiko (Овощи России, 2018)
Actual problem in breeding onion (Allium cepa. L) is the identification of cytoplasm type in varieties and F1 hybrids. To create a parent sterile fixing line, is required a cytoplasm of type N. However, heterozygous F1 hybrids and new onion varieties obtained from subsequent generations from F1 fertility hybrids that possess economically valuable traits and meet market requirements are not suitable for creating a sterile fixing line from them, because all hybrid plants has 100% S-cytoplasm or T-cytoplasm type. In order to determine the most desirable parent component with subsequent use in the selection process, the Laboratory of Selection and Seed Production of Onion Cultures of the Gavrish company conducted a phenotypic and molecular analysis of collection samples of onions for the feature of male sterility. The material for research was grown according to the generally accepted technologies for the zone in the city of Krymsk, Krasnodar Territory. Phenotypic analysis of the manifestation of the "male sterility" feature was carried out with the help of visual analysis. As a result of the work, were identified varieties and F1 hybrids that can be used as genetic sources for the creation of new sterile lines and lines of sterility fixers, as well as samples to be used as pollinators. In the future, these lines will be used to create heterotic F1 hybrids with high indicators of economic characteristics with given properties.